Standard versus combined chemical, mechanical, and heat decontamination of hospital drains harboring carbapenemase-producing organisms (CPOs): A randomized controlled trial. (8th October 2021) - Jamal, Alainna J.; Pantelidis, Rajni; Sawicki, Rachael; Li, Angel X.; Chiu, Wayne; Morrison, Deborah; Marshman, John; Baqi, Mahin; Richardson, David; McGeer, Allison J.; Borgia, Sergio
Abstract: We sought to determine whether combined chemical, mechanical, and heat cleaning was superior to standard cleaning for the decontamination of 32 sink and shower drains harboring carbapenemase-producing organisms (CPOs). Of 16 intervention drains, 10 (63%) were decontaminated until day 7 versus 1 (5%) of 16 comparator drains ( P = .002). Intensive cleaning may be useful if administered repeatedly in drain-associated CPO outbreaks.